A Structural Model of Depression Based on Early Maladaptive Schemas, Resilience and Perceived Social Support with the Mediating Role of Self-Compassion and Hope in men and women with cancer - Shahbeik, Soroush; Moazedian, Ameneh; Sabahi, Parviz; Khanmohammadi Otaghsara, Arsalan (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of the present study was to investigate the depression prediction model based on early maladaptive schemas, resilience and perceived social support by considering the mediating role of self-compassion and hope in men and women with cancer. Methods: The research method was descriptive correlation. The statistical population in this study included all cancer patients referred to Imam Khomeini and Milad hospitals in Tehran. The sample size was 300 patients were selected based on inclusion and exclusion criteria. Research instruments included the Nef Self-Sufficiency Questionnaire (2003), Young’s Early maladaptive Schemas Questionnaire (1998), Connor-Davidson Resilience Questionnaire (2005), Zimet et al.’s Perceived Social Support Questionnaire (1988), Beck depression Scale (1961) And Snyder (1991) Hope Questionnaire. The collected data were analyzed by structural equation modeling. Results: The finding of data analysis showed that the depression prediction model based on initial maladaptive schemas, resilience and perceived social support, considering the mediating role of self-compassion and hope based on experimental data, has a good fit. Also, the direct and indirect effects of early maladaptive schemas, perceived resilience and social support were considered (p <0.05) regarding the mediating role of self-care and hope on the depression of cancer patients. Self-compassion directly affects the depression of cancer patients (p <0.05). Hope also directly affects the depression in cancer patients (p <0.05). Conclusion: According to the research results, in order for cancer patients to function properly, on the one hand, it is necessary to have modified maladaptive schemas, on the other hand, their treatment t should be based on improving resilience and perceived social support.